Habitats - Brundle, Harriet; Kissock, Heather (Awesome infographics., 2021)
Presents a series of infographics that reveal fun facts about each of the world's habitats, such as deserts, grasslands, and mountains. Includes a discussion of habitat construction, destruction, and conservation, as well as animal adaptations to extreme conditions.